Lehramt der Päpste und Lehramt der Theologen im konfessionellen Streit des 16. Jahrhunderts - Unterburger, Klaus (Historisches Jahrbuch, 2013)
The paper seeks to prove that modern subjectivism did not lead to the Reformation break with medieval ecclesiastical authority. Rather, the medieval tension between theological and pastoral magisterium already provided those concepts, which in the 16th century, came into open conflict with each other. After the positions in this debate had become irreconcilable, the specific denominational ecclesiologies were subsequently formed. The starting point of the argument is that Martin Luther rarely described himself as a "reformer", but rather placed great emphasis on the title of "Doctor of Divinity". The basis of the theology's claim of validity (formed primarily in the 13th century) was the character of theology as a science with its own responsibility, authority, and freedoms, distinct from the pastoral magisterium of bishops and pastors. For this self-understanding as a theologian, Luther formulated his theological insights to repentance, grace, indulgence, and theological method in this series for public disputations. When Dominican theological opponents accused him of heretical teachings contrary to the papal and episcopal magisterium, Luther saw them as an envious, rival school of theological thought - especially in regards to the authority of the Pope and the Councils. The Pope and Council are to be obeyed, but the iudicium on a historic council or on a concrete papal pronouncement is the task of theological reason. Here, Luther employed the tradition of theology and canon law of the Middle Ages. Tue tension between the two magisteria became an irreconcilable conflict. Subsequently, the effort to prevent future conflicts between auctoritas and ratio became an important factor in the formation of confessional ecclesiologies. The Lutheran and Reformed Churches tried to subordinate jurisdiction and administration of the sacraments to theological insight and preaching. The Catholic Church attempted to maintain security by closing the doors against any theological criticism of papal teaching. Only the pope and the bishops have a binding judgment about faith and Scripture; the legitimacy of a council is secured solely by the popes, who - in contrast to the prevailing opinion of the Middle Ages - cannot deviate from faith.